Instalación y montaje de un sistema de compresión de gas natural para el transporte y distribución en municipios de los departamentos de Cauca y Nariño (2021)
This degree work deals with installation and assembly of a compression system of natural gas which was implemented to improve the transport and distribution of energy in some municipalities of the department of Cauca and Nariño.